Possibility to Combine Exergy with other Process Integration Methods for a Steelmaking Case - Elfgren, Erik; Grip, Carl-Erik; Wang, Chuan; Karlsson, Jonny (Luleå tekniska universitet, Energivetenskap, 2010)
The energy system of Luleå consists of the steel plant, a local CHP using process gases from the plant and the district heating system. Process integration work to improve the efficiency of the system is presently carried out by mathematical programming using a MILP tool (reMIND). Further improvements would need an improved possibility of the tool to consider the thermodynamic quality of the energy flows. This project aims to include exergy parameters in the node equations and object functions. This has been carried out for a test case, including a part of the system. Programming principles and some results are described. Validerad; 2010; 20110209 (ysko)